New insights for risks of chlorophenols (CPs) exposure: Inhibition of UDP-glucuronosyltransferases (UGTs). (September 2018) - Yang, Kai; Fu, Zhi-Wei; Cao, Yun-Feng; Li, Sai-Nan; Du, Zuo; Sun, Xiao-Yu; Liu, Yong-Zhe; Yang, Kun; Fang, Zhong-Ze
Abstract: Chlorophenols (CPs) are important pollutants extensively utilized in industry, agriculture and forestry. The present study aims to determine the inhibition of CPs on the activity of the important phase II drug-metabolizing enzymes (DMEs) UDP-glucuronosyltransferases (UGTs). 100 μM of fourteen CPs were used for preliminary screening using in vitro incubation. Furthermore, half inhibition concentration (IC50 ) and inhibition kinetics were determined for CPs with significant inhibition towards UGT isoforms. In silico docking was used to explain the inhibition difference among CPs. Multiple UGT isoforms were inhibited by CPs. In silico docking showed that higher free binding energy due to hydrophobic interactions of 2.4-Dichlorophenol (2.4-DCP) or 4-Chloro-3-methylphenol (4C3MP) with UGT1A9 contributed to stronger inhibition potential of 2.4-Dichlorophenol (2.4-DCP) or 4-Chloro-3-methylphenol (4C3MP) towards UGT1A9 than 4-CP. Pentachlorophenol (PCP) was chosen as the representative CPs to determine the IC50 value towards UGT1A6, UGT1A9 and UGT2B7. IC50 was calculated to be 0.33 μM, 0.24 μM and 31.35 μM for the inhibition of PCP towards UGT1A6, UGT1A9 and UGT2B7. PCP was demonstrated to show competitive inhibition towards UGT1A6, UGT1A9 and UGT2B7, and the inhibition kinetic parameters (Ki) was calculated to be 0.18 μM, 0.01 μM and 5.37 μM for the inhibition of PCP towards UGT1A6, UGT1A9 and UGT2B7. All these information will be beneficial for elucidating the risk of CPs exposure from a new perspective. Graphical abstract: Image 1 Highlights: Chlorophenols (CPs) showed inhibition on UGTs. Methyl group introduction significantlyincreased inhibition towards UGT1A6, -1A7, and -1A9. The numbers of chloride atoms affect the inhibition potential.